Exploring Community Readiness to Adopt Mobility as a Service (MaaS) Scheme in the City of Thessaloniki - Panagiota Mavrogenidou; Apostolos Papagiannakis (Urban Science, 2024)
Mobility as a Service (MaaS) is a new mobility solution that brings together different modes of transportation, such as car-sharing, public transport, taxis, and bicycles, to create personalized service packages for commuters. The present study aims to identify key factors affecting the adoption of a Mobility as a Service system, and to explore the extent to which a local community is ready to accept the implementation of MaaS. The case study investigates the city of Thessaloniki, which is the second largest urban agglomeration in Greece. This study applies a triangulation approach by combining quantitative and qualitative analysis, providing a comprehensive understanding of the opportunities and the challenges arising with the implementation of a MaaS system in the city of Thessaloniki. Furthermore, the utilization of MaaS as a tool for vulnerable people, a crucial aspect that has not been analyzed properly in the existing literature, is examined. A quantitative survey analysis was conducted, inferential statistics were applied, and a binary logistic regression model was developed to determine the significant characteristics that most affect citizens’ willingness to use a MaaS system. In addition, stakeholders were interviewed to examine their readiness to promote and collaborate for the development of a MaaS system. Results showed that age, driving license, daily time spent on urban trips, the frequency of commuting as car passenger or by public transport (PT), previous usage of a MaaS system, and the number of family members seem to be the most influential factors of citizens’ choice to adopt MaaS. For stakeholders, the quality of service provided, and the user friendliness of the system are necessary prerequisites. The findings reveal that the views of residents and stakeholders provide some positive foundations for the development of a MaaS system in the city.